Stability Control Structure of Hovercraft Prototype Utilising PID Controller - Bhaskara Rao. Yenugula; Md. Zia-ur-Rahman (Bulletin of Electrical Engineering and Informatics, 2017)
Hovercraft is a method of transportation as an option for clients who remain on the waterway and swamp surface. The issue with hovercraft is when dubious climate and natural condition, e.g. wind speed and wave tallness exasperate solidness of hovercraft to jeopardise the driver. We propose an approach to keep up adjust of the hovercraft by controlling the focal point of gravity (PG) to be determined position. The controller monitors the position of load to change the position. A 6-DOF IMU Sensor MPU 6050 was utilised to create information as an examination with setpoint. PID control strategy was employed. The test outcome demonstrates that the model of air cushion vehicle could keep its adjust the axis orientation of the roll in spite of the fact that it was less compelling in the pitch pivot direction.